2019
DOI: 10.1530/erp-19-0020
|View full text |Cite
|
Sign up to set email alerts
|

Practical tips and tricks in measuring strain, strain rate and twist for the left and right ventricles

Abstract: Strain imaging provides an accessible, feasible and non-invasive technique to assess cardiac mechanics. Speckle tracking echocardiography (STE) is the primary modality with the utility for detection of subclinical ventricular dysfunction. Investigation and adoption of this technique has increased significantly in both the research and clinical environment. It is therefore important to provide information to guide the sonographer on the production of valid and reproducible data. The focus of this review is to (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 41 publications
0
40
0
11
Order By: Relevance
“…The analysis of LV deformation including circumferential strain and rotation may improve the echocardiographic diagnostic approach in AM [ 24 , 27 , 28 ]. However, the use of myocardial deformation is not yet widely implemented in patients with AM [ 36 , 37 ]. Recently, the authors of the present study demonstrated the feasibility to define deformation patterns for radial and circumferential strain as well as rotation in a cohort of healthy volunteers and professional athletes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of LV deformation including circumferential strain and rotation may improve the echocardiographic diagnostic approach in AM [ 24 , 27 , 28 ]. However, the use of myocardial deformation is not yet widely implemented in patients with AM [ 36 , 37 ]. Recently, the authors of the present study demonstrated the feasibility to define deformation patterns for radial and circumferential strain as well as rotation in a cohort of healthy volunteers and professional athletes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…RV functional reserve may be assessed by measuring TAPSE, RVS’, and RV fractional area change at rest and during stress ( 52 ). RV longitudinal strain may also be assessed during rest and stress, although this may become less reliable at heart rates > 100 bpm due to reduced frame rate ( 53 ). A failure to augment these indices suggests impaired RV functional reserve, which has been associated with worse outcomes in patients with left-sided valve disease ( 52 ).…”
Section: Stress Echocardiographymentioning
confidence: 99%
“…The best single cardiac cycle was selected for analysis as validated by several studies. 15,16 After the tracing was complete, the images were played frame by frame, and the tracing was manually adjusted if necessary. This software measures the different segmental speckle strains and strain rates.…”
Section: Speckle-tracking Echocardiographymentioning
confidence: 99%